2011
DOI: 10.1016/j.molcel.2011.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Systematic and Quantitative Assessment of the Ubiquitin-Modified Proteome

Abstract: Summary Despite the diverse biological pathways known to be regulated by ubiquitylation, global identification of substrates that are targeted for ubiquitylation has remained a challenge. To globally characterize the ubiquitin-modified proteome (ubiquitinome), we utilized a monoclonal antibody that recognizes diglycine (diGly) containing isopeptides following trypsin digestion. We identify ~19,000 diGly modified lysine residues within ~ 5000 proteins. Using quantitative proteomics we monitored temporal changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

97
1,445
7
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,459 publications
(1,597 citation statements)
references
References 34 publications
97
1,445
7
6
Order By: Relevance
“…The HECT E3 ligases transiently bind with Ub by forming a thioester intermediate, before Ub transferred to substrate, but RING ligases act as scaffold, and it promotes the direct transfer of Ub to substrate by bringing the E2‐bound Ub close to substrate 13. The proteomic studies have shown that all types of polyubiquitination co‐exist in cells 14, 15. Lys48‐linked chains are the most abundant linkage type (often > 50% of all linkages) found in cells that are primarily involved in transfer of substrate proteins to the 26S proteasome for degradation 16.…”
Section: Ubiquitin Modificationsmentioning
confidence: 99%
“…The HECT E3 ligases transiently bind with Ub by forming a thioester intermediate, before Ub transferred to substrate, but RING ligases act as scaffold, and it promotes the direct transfer of Ub to substrate by bringing the E2‐bound Ub close to substrate 13. The proteomic studies have shown that all types of polyubiquitination co‐exist in cells 14, 15. Lys48‐linked chains are the most abundant linkage type (often > 50% of all linkages) found in cells that are primarily involved in transfer of substrate proteins to the 26S proteasome for degradation 16.…”
Section: Ubiquitin Modificationsmentioning
confidence: 99%
“…This technique was used in three landmark papers from the Gygi, Mann and Elledge laboratories to identify the largest set, to date, of ubiquitin substrates [41,89,90]. Although the identification rate was initially in the range of 300 to 800 ubiquitination sites [81,88] employment of peptide fractionation, such as isoelectric focusing or strong cation exchange chromatography, improved the identification rates to 10000 -20000 ubiquitination sites in one study [41,[91][92][93].…”
Section: Ubiquitin Site Identification Using Peptide-specific Antibodiesmentioning
confidence: 99%
“…Although the identification rate was initially in the range of 300 to 800 ubiquitination sites [81,88] employment of peptide fractionation, such as isoelectric focusing or strong cation exchange chromatography, improved the identification rates to 10000 -20000 ubiquitination sites in one study [41,[91][92][93]. Using β-interferon stimulation to stimulate ISG15 expression as a positive control, Kim et al estimated the contribution of ISGylation (Figure 2) of substrates to the total number of di-glycine modified peptides, and concluded that a negligible portion of the total modified peptide population can be attributed to ISG15 modification [89]. In the same study, a general DUB was used to cleave all ubiquitin moieties from their substrates leaving only the sites modified by Nedd8.…”
Section: Ubiquitin Site Identification Using Peptide-specific Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1997; Kim et al . 2011). In this review, we present recent findings related to monoubiquitylation, with a focus on the best‐studied mammalian systems, and we provide an overview of monoubiquitylated proteins and the effects of monoubiquitylation on substrates categorized according to their function.…”
Section: Introductionmentioning
confidence: 99%